An Experimental Study On Antihypertensive Activity Of Garcinia Atroviridis Fruit Extracts - Kharuddin, Fatim (2014)
Garcinia atroviridis (GA) plant has been used as a traditional medicine for treating earache, throat irritation, cough, dandruff and stomach disorders associated with pregnancy and hypertension. In the present study, the anti-hypertensive effectsguided extraction and fractionation of GA fruit were carried out in an attempt to find the most active chemical component. The fruit of this plant was dried, ground and serially extracted with petroleum ether, chloroform, methanol and water. The extracts were dried under reduced pressure and later freeze-dried. The vasodilator effect of the extracts was examined on isolated rat aortic ring preparation. The petroleum ether extract was found to be the most potent in relaxing PE pre-contracted aortic rings. The petroleum ether extract was then fractionated with n-hexane and dichloromethane. The n-hexane fraction (2 mg ml-1) was found to be the most active in relaxing the aortic ring. Removal of the endothelium of the aortic ring did not abolish the relaxing property of petroleum ether extract which suggests that the relaxing effect of the extract is not endothelium dependent. Orally administered all of GA extracts (1 g kg-1) significantly reduced the systolic blood pressure and heart rate of spontaneous hypertensive (SH) rats which support the antihypertensive effect of GA fruit. In anaesthetized rats, the intravenous administration of methanol and water extracts of GA dose-dependently reduced mean arterial pressure (MAP), systolic pressure (SP), diastolic pressure (DP) and heart rate (HR) of SD rats.